INTERPRETING A POEM OF BEN JONSON, â€œSONG: TO CELIAâ€ - Effendie, Nanik Mariana (LET: Linguistics, Literature and English Teaching Journal, 2012)
ABSTRACTDiscourse analysis is analysis of language in use (Brown and Yule, 1983). How the language-users interpret what other language-users intend to convey and how they make sense of what they read in texts, understand what speakers mean despite what they say, recognize connected as opposed to jumbled or incoherent discourse, and successfully take part in that complex activity called conversation. A poem can be interpreted through discourse analysis approach (Brown and Yule, 1983). Using this approach, the meaning of a poem can be revealed exactly the same as or very close to what the poet want to say or send the message. This article tries to interpret ?Song: To Celia?, one of Ben Jonson?s poems through knowledge of the world or schema, context and coherence. Knowledge of the world or Schema plays key roles in many cognitive processes. They help us pay attention, comprehend, interpret, remember, make inferences, set expectations, reason, solve problems, understand language structures, read, write, explain what we know, and have a sense of humor. To interpret this poem, knowledge about love is important, and also the schemata about who the speakers and the listeners are. The speaker in "Song: To Celia" is a man who opens with a plea for his lady to express her love by gazing upon him. And the listener of this poem is an imaginated listener, a lady, who refuses the speaker?s love. According to Hymes (1964), there are nine contexts in discourse analysis but ?context of using code? is used to understand the symbols used in this poem, such as: ?wine? symbolizes something better, nicer, and intoxicating and ?a rosy wreath? symbolizes the greatest love of someone. And ?context of genre? is also used in  understanding the poem itself or the terms of the poem, likes ?figurative languages?. In this poem, there are two kinds of figurative languages, personification and allusion Coherence which has to do with the meaning of the text (discourse) and context, may refer to elements of knowledge or to cognitive structures that do not have a linguistic realization but are implied by the language used, and thus influence the reception of the message by the interlocutor. Coherence of this poem can be seen from the unity of the words which produces meaning. As a whole the meaning of this poem is telling about the reflection of admiration a man toward his lady love, and this man loves her very much. The speaker (the man) asks the listener (the lady love) look at him only with her eyes to refill her secret to him, and he will do the same